Relasi Psikologis Dokter-Pasien dalam Layanan Kesehatan: Persepsi, Komunikasi, Empati dan Unsur Kepercayaan - Moordiningsih Moordiningsih (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2006)
Psychological relation between patient and his/her doctor could help the patient’s healing process. This article is part of research about doctor’s decision making which try to comprehend doctor-patient psychological relationship. This qualitative research involved 11 specialist doctors in Surakarta as informen. This research found that psychological aspects of doctor-patient relationship consist of physical attraction, cognitive schemas, stereotype and doctor’s memory. Another doctor’s psychological aspects that have its role on doctor-patient relation are communicationn skill, inteligence capacity, empathy, ability to build patient trust and positive values. Kata kunci: relation between patient and his/her doctor